A multicentre double‐blind, double‐dummy, randomised study of recombinant human thrombopoietin versus eltrombopag in the treatment of immune thrombocytopenia in Chinese adult patients. (16th September 2021) - Mei, Heng; Xu, Min; Yuan, Guolin; Zhu, Feiyue; Guo, Jingming; Huang, Ruibin; Qin, Jun; Lv, Tingting; Qin, Fangmei; Cai, Huili; Yin, Ping; Qin, Tingting; et al.
Summary: We performed a double‐blind, double‐dummy controlled study to compare the efficacy between recombinant human thrombopoietin (rhTPO) and eltrombopag in rapidly increasing the platelet counts in Chinese patients with immune thrombocytopenia (ITP). A total of 96 patients diagnosed with ITP for ≥6 months who had baseline platelet counts of <30 × 10 9 /l were randomly assigned (1:1 ratio) to receive eltrombopag 25 mg/day or rhTPO 300 u/kg for 2 weeks. Compared with the eltrombopag group, a significantly higher proportion of patients in the rhTPO group achieved platelet counts of ≥50 × 10 9 /l [75·00% (36/48) vs. 43·75% (21/48), P  = 0·003] or complete response (64·58% vs. 25·00%) on day 15. Moreover, a higher proportion of patients in the rhTPO group either had platelet counts that rapidly increased to twice that of baseline and with platelet counts of ≥30 × 10 9 /l, or reached ≥50 × 10 9 /l at least once when analysed on day 9, 12, and 15. However, upon discontinuation of the treatment, the platelet counts reduced to the baseline within 1 week in the rhTPO group, but on the fourth week in the eltrombopag group. Adverse events were similar in patients given rhTPO and eltrombopag. To conclude, rhTPO is superior to eltrombopag at 25 mg/day in rapidly increasing platelet counts in patients with ITP (ClinicalTrials.gov Identifier: NCT03771378).